Il peso dell'infanzia Una ricerca sociologica su abitudini alimentari e obesità - Plava, Annalisa (Benessere Tecnologia Società, 2023)
Childhood obesity is an endemic, growing and worrying phenomenon driven by multiple and interdependent causes. It is, therefore, one of the greatest challenges of the 21st century, both from a medical and social point of view. In fact, according to sociological life course approach, childhood and early adolescence years have a great influence on a person's future health. This work, based on solid empirical research conducted in Rimini, highlights the role that diet and lifestyle play in the mechanisms that lead to weight excess among primary school children, also including dimensions related to stigma, body perception and the relationship between the vulnerable population and body weight. In particular, through a sociological lens, it is shown how educational policies aimed at healthy lifestyles can steer children and families towards a balanced diet.